CK2α/CSNK2A1 Induces Resistance to Doxorubicin through SIRT6-Mediated Activation of the DNA Damage Repair Pathway - Hussein, Usama Khamis (Cells, 2021)
CK2α/CSNK2A1 is involved in cancer progression by phosphorylating various signaling molecules. Considering the role of CSNK2A1 in cancer progression and the phosphorylation of SIRT6 and the role of SIRT6 in chemoresistance through the DNA damage repair pathway, CSNK2A1 and SIRT6 might be involved in resistance to conventional anti-cancer therapies. We evaluated the expression of CSNK2A1 and phosphorylated SIRT6 in the 37 osteosarcoma patients and investigated the effects of CSNK2A1 and the phosphorylation of SIRT6 on Ser338 on resistance to the anti-cancer effects of doxorubicin. Higher expression of CSNK2A1 and phosphorylated SIRT6 was associated with shorter survival in osteosarcoma patients. U2OS and KHOS/NP osteosarcoma cells with induced overexpression of CSNK2A1 were resistant to the cytotoxic effects of doxorubicin, and the knock-down of CSNK2A1 potentiated the cytotoxic effects of doxorubicin. CSNK2A1 overexpression-mediated resistance to doxorubicin was associated with SIRT6 phosphorylation and the induction of the DNA damage repair pathway molecules. CSNK2A1- and SIRT6-mediated resistance to doxorubicin in vivo was attenuated via mutation of SIRT6 at the Ser338 phosphorylation site. Emodin, a CSNK2A1 inhibitor, potentiated the cytotoxic effects of doxorubicin in osteosarcoma cells. This study suggests that blocking the CSNK2A1-SIRT6-DNA damage repair pathway might be a new therapeutic stratagem for osteosarcomas.